Atrial Fibrillation, Oral Anticoagulants, and Concomitant Active Cancer: Benefits and Risks - Atterman, Adriano; Friberg, Leif; Asplund, Kjell; Engdahl, Johan (TH Open, 2021)
Aim To determine to what extent active cancer influences the benefit–risk relationship among patients with atrial fibrillation receiving oral anticoagulants for stroke prevention.Methods In this cohort study of all patients with atrial fibrillation in the Swedish Patient register during 2006 to 2017, 8,228 patients with active cancer and 323,394 without cancer were followed up to 1 year after initiation of oral anticoagulants. Cox regression models, adjusting for confounders and the competing risk of death, were used to assess risk of cerebrovascular and bleeding events.Results Among patients treated with oral anticoagulants, the risk for cerebrovascular events did not differ between cancer patients and noncancer patients (subhazard ratio [sHR]: 1.12, 95% confidence interval [CI]: 0.98–1.29). Cancer patients had a higher risk for bleedings (sHR: 1.69, CI: 1.56–1.82), but not for fatal bleedings (sHR: 1.17, CI: 0.80–1.70). Use of nonvitamin K oral anticoagulants was associated with lower risk of both cerebrovascular events and bleedings compared with warfarin.Conclusion Patients with atrial fibrillation and active cancer appear to have similar net cerebrovascular benefit of oral anticoagulant treatment to patients without cancer, despite an increased risk of nonfatal bleedings. Use of nonvitamin K oral anticoagulants was associated with lower risk of all studied outcomes.
Keywords: atrial fibrillation; stroke prevention; cancer